In vitro activity of mecillinam against anaerobic bacteria. - Steinkraus, G E (1980)
A microtiter broth dilution method was employed to determine the in vitro activity of mecillinam against 201 recent clinical isolates of anaerobic bacteria. Both the anerobic gram-positive and anaerobic gram-negative bacilli displayed a wide range of minimal inhibitory concentrations of mecillinam; most strains were resistant to the antibiotic. The anaerobic cocci exhibited a narrower range of minimal inhibitory concentrations than were observed with other anaerobes, but also exhibited mecillinam resistance. As a single durg, mecillinam does not appear to be an effective antimicrobial agent against anaerobic bacteria.